Normas y reglas de comportamiento para la convivencia - Tipán Defaz, Martha Cecilia (2020)
Assertive communication allows mediating difficulties and negative behaviors, helping to maintain a harmonious coexistence among classmates. The present research study on the policies and rules of behavior of coexistence of level 2 preschool children, in the "Juan de Salinas" School, is carried out based on a direct observation of the problem. In this study, an exploratory, diagnostic and descriptive investigation was improved, based on qualitative and quantitative techniques, which, by comparing and contrasting theories, helped to gather information about the research problem. Once the theories of coexistence policies and rules of behavior have been analyzed, a methodological guide is developed to improve children's coexistence.